Penggunaan Teknologi Informasi (TI) Dalam Mengoptimalkan Keterlibatan Siswa Di Perpustakaan Lensa Literasi SDN Wonokusumo VI/45 Surabaya - Eka Fitria Novita Sari (JDP (JURNAL DINAMIKA PENDIDIKAN), 2025)
The use of Information Technology to Optimize Student Engagement in the "Lensa Literasi" School Library at SDN Wonokusumo VI/45 is a study aimed at exploring how the integration of information technology (IT) can affect student engagement in school libraries. This research adopts a mixed-method approach by combining quantitative and qualitative methods. The quantitative study was conducted through a survey of 200 students using purposive sampling techniques to understand the frequency of IT usage, the types of technology used, and their perceptions of engagement in the library. The results showed that most students use computers and the internet to search for information, while the use of e-books and library mobile applications is also significant. The qualitative study involved in-depth interviews with 20 participants, including students, librarians, and teachers, to explore their experiences using IT in the library, its impact on learning, and the challenges faced in its implementation. Thematic analysis of the interviews revealed that IT integration enhances information accessibility, students' learning motivation, and the effectiveness of library services. The findings of this study highlight the importance of strategic planning in integrating IT, developing adequate infrastructure, and providing continuous training for librarians and students. Practical recommendations include improving technical support, developing IT-based student engagement programs, and conducting regular evaluations to ensure the sustainability and effectiveness of IT integration in school libraries. This study is expected to provide significant contributions to educational policies and library management practices that focus on the use of technology to enhance the quality of education and student literacy